Black Hole Attack Prevention Techniques in MANET: A Review (International Journal of Engineering and Computer Science, 2014)
Mobile ad-hoc networks (MANET) is a major next generation wireless technology. Dynamically and arbitrarily located nodes communicate to each other to form a Mobile Adhoc Network. MANET is more vulnerable to various types of attack than wired network. Black hole attack is more severe threat to MANET than any other attack. Prevention of Black hole attack is done by finding the malicious node before any harm can be done. Different techniques are proposed to prevent this type of attack. In this paper these techniques are studied with their advantages and disadvantages.